Evaluation of the Genotoxicity of Almond Hull: Implications for Its Use as a Novel Food Ingredient - Yuyang Yao; Juer Liu; Qiming Miao; Xinyue Zhu; Wei Hua; Na Zhang; Guangwei Huang; Xiangyang Lin; Shengquan Mi; Yanling Cheng; Roger Ruan (Foods, 2024)
Almond hull, a substantial byproduct comprising more than half of almond fresh weight, has recently gained attention due to its functionality and sustainability benefits. Despite heightened interest, information regarding its toxicity remains limited. In order to assess its genotoxic potential, we conducted Good Laboratory Practice-compliant in vitro and in vivo studies following Organization for Economic Co-operation and Development (OECD) guidelines. No evidence of toxicity or mutagenicity was observed in a bacterial reverse mutation assay using five tester strains, evaluating almond hull at concentrations up to 5 mg/plate, with or without metabolic activation. Almond hull did not induce chromosome structural damage in a chromosome aberration assay using Chinese hamster ovary cells, nor did it cause any spermatogonial chromosomal aberration in tested male BALB/c mice. To evaluate its ability to induce DNA damage in rodents, a combined micronucleus assay was conducted in KM mice of both sexes. Almond hull was administered at doses of 1250, 2500, and 5000 mg/kg/day via gavage once daily for 2 days. No adverse effects of almond hull were observed in the micronucleus assay. Our results indicate no evidence of the genotoxic potential of almond hull administered up to the maximum concentrations of 5 g/kg, as recommended by OECD guidelines.